Teacher training in Education: thought and experience - Perez, Deivis [UNESP]; Oliveira, Sabrina Orgado (Univ Metodista Piracicaba-unimep, 2015)
This research was devoted to the analysis of the teachers' perceptions and reflections on teacher training. This question was examined by means of data collection and discussion of the case of three educators who worked as teachers of the basic education in the kindergarten and elementary levels. Specifically, we sought to identify and examine what the volunteers of the study understand and think of teacher training with regard to the following dimensions: a) the historical interest and delimitation of the concept of professional teacher training; b) the space occupied by teachers within the Science of Education; c) the personal meaning attributed to the training experienced in the undergraduate course in Education. The results show that teachers consider Pedagogy as a sub-area of the Science of Education, to which teacher training is linked. We also observed a strong rejection to the term training, perceived as human development for professional life marked by authoritarian and forceful actions, as opposed to the ideal of partnership between teachers and their students. As to how the training was experienced within the course of Education, at times it was considered too theoretical and, in other situations, as facilitating the appropriation of relevant knowledge for teacher's work.
Keywords: EDUCATION; TEACHER TRAINING; SCIENCE OF EDUCATION